Interpreting Susan Sontag's essays radical contemplative - Fulk, Mark K., 1968- (New York, NY : Routledge, 2021)
Interpreting Susan Sontag's Essays: Radical Contemplative offers its readers a scholarly examination of her essays within the context of philosophy and aesthetic theory. This study sets up a dialogue between her works and their philosophical counterparts in France and Germany, including the works of Hannah Arendt, Jacques Derrida, Roland Barthes, and Walter Benjamin. Artists and concepts discussed in relation to Sontag's essays include the works of Andy Warhol, Pop Art, French New Wave Cinema, the music of John Cage, and the cinematic art of Robert Bresson, Leni Riefenstahl, Ingmar Bergman, and Jean-Luc Godard. Her aesthetic formalism is compared with Harold Bloom, and this is the first volume to examine her late works and their position within the American events of 9/11/01 and the War on Terror(ism).
OCLC-licensed vendor bibliographic record.
Keywords: Sontag, Susan, -- 1933-2004 -- Criticism and interpretation; LITERARY CRITICISM / American / General; PHILOSOPHY / History & Surveys / Modern